1971
DOI: 10.1128/am.21.4.693-697.1971
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Sanitation: the Massive Bacterial Contamination of the Wet Mop

Abstract: Following the demonstration of massive spread of bacterial contamination throughout the hospital by the wet-mopping techniques in use, quantitative studies were undertaken to determine the source of contamination and to institute measures of control. It was found that mops, stored wet, supported bacterial growth to very high levels and could not be adequately decontaminated by chemical disinfection. Laundering and adequate drying provided effective decontamination, but build-up of bacterial counts occurred if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Mops and reusable cleaning cloths are regularly used to achieve low-level disinfection on environmental surfaces. However, they often are not adequately cleaned and disinfected, and if the water-disinfectant mixture is not changed regularly (e.g., after every three to four rooms, at no longer than 60-minute intervals), the mopping procedure actually can spread heavy microbial contamination throughout the health-care facility [8]. Westwood and Mitchell also found that standard laundering provided acceptable decontamination of heavily contaminated mop heads, but chemical disinfection with a phenolic products was less effective.…”
Section: Introductionmentioning
confidence: 99%
“…Mops and reusable cleaning cloths are regularly used to achieve low-level disinfection on environmental surfaces. However, they often are not adequately cleaned and disinfected, and if the water-disinfectant mixture is not changed regularly (e.g., after every three to four rooms, at no longer than 60-minute intervals), the mopping procedure actually can spread heavy microbial contamination throughout the health-care facility [8]. Westwood and Mitchell also found that standard laundering provided acceptable decontamination of heavily contaminated mop heads, but chemical disinfection with a phenolic products was less effective.…”
Section: Introductionmentioning
confidence: 99%